Tendencias de las publicaciones sobre humanismo en enfermería : un análisis bibliométrico (2024)
Humanism has significantly shaped modern nursing practices by emphasizing on the crucial value of providing patient-centered care and acknowledging the innate worth of human dignity. That is why this paper aims to explore and assess the existing framework of knowledge within publications that address humanism in nursing, as well as trace its evolutionary trajectory. The present document shows the results of a descriptive bibliometric study based on a data retrieval conducted from the Web of Science (WoS) Core Collection database and its subsequent analysis made using Excel and VOSviewer. The study encompassed 135 documents published from 1993 to 2021 in 82 journals, authored by 390 researchers from 33 countries. Notably, 79.3% of these works were classified as original articles, 53.3% belonged to the nursing category, and 86.7% were published in English. The existence of a strong connection between humanism, ethics, care, and nursing education was observed in all the works analyzed.